A STUDY ON THE EFFECTIVENESS OF HEALTH INSURANCE IN MINIMISING HEALTHCARE COSTS FOR RURAL FAMILIES IN TIRUVANNAMALAI - 1. Mr. S. SRINIVASAN , 2. Dr.A.M.AYYOTHI (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This study examines the effectiveness of health insurance in minimizing healthcare costs for rural families in Tiruvannamalai District, Tamil Nadu. Despite the implementation of various government-sponsored schemes such as Ayushman Bharat and CMCHIS, rural households continue to face high out-of-pocket healthcare expenditures. The study aims to evaluate awareness levels, challenges in availing benefits, and the overall impact of health insurance on reducing financial burden during medical emergencies. Using a descriptive and analytical research design, data were collected from 150 respondents across selected rural blocks through structured questionnaires and interviews. Statistical tools including simple percentage analysis and t-tests were employed for data analysis. Findings reveal that while access to empanelled hospitals and trust in insurance providers is high, significant issues persist in claim settlement processes. The study highlights the need for improved awareness, streamlined claim procedures, and policy interventions to enhance the effectiveness of health insurance schemes in safeguarding rural families from financial distress.